The Influence of Price, Location and Service on Purchase Decisions at the Air Sebakul NRL Minimarket, Bengkulu City - Holil Holil; Neri Susanti; Rina Trisna Yanti (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
The purpose of this study was to determine the effect of price, location and service on purchasing decisions at the NRL Air Sebakul Minimarket, Bengkulu City. The sample in this research is 95 consumers. The sampling technique used was saturated sample by using the entire research population as the research sample. The data is processed in the form of numerical data (numbers) using a Likert scale. Data collection methods in this study were questionnaires and literature study. The data is processed using spss for windows version 20.0. Methods of data analysis using quantitative methods, namely by using multiple linear regression analysis. The results of the study prove that the price, location and service variables have a significant influence on the dependent variable, namely purchasing decisions at the Air Sebakul NRL Minimarket Bengkulu City. The biggest significant influence on purchasing decisions at the Air Sebakul Minimarket, Bengkulu City, is partially the service variable with a standard beta coefficient of 5.849, the location variable with a beta coefficient of 5.010 then the price variable with a beta coefficient of 4.623 and simultaneously Fcount 57.834. From the results of this analysis, it can be concluded that service and location are the dominant factors that have the greatest influence on the tendency of purchasing decisions at the Air Sebakul Minimarket, Bengkulu City